(untitled) (Third Sector Social Economic Review, 2019)
Lately retail industry differentiate consumers consuming habits. Shopping centers not only are new trend in retailing, but also they impact and shape buying behaviour of consumers. Shopping centers managers try to fulfil consumers needs and wants in a better way. Shopping centers have to create suitable shopping environment for their customers, to make them satisfied. The aim of this work is designating the impact of shopping center’s environment on shopping center’s patronage and customer satisfaction. In this study, in Ankara 435 people who visit shopping centers completed the questionnaires. As a result of research, it is identified that shopping center’s environment how impacts shopping center’s patronage and customer satisfaction.